Patients' and providers' perspectives of a dose administration aid strategy to improve cardiovascular disease prevention in Australian primary healthcare - Kanika Chaudhri; Hueiming Liu; Anthony Rodgers; Richard Day; Emily R. Atkins; Sonali R. Gnanenthiran (BMC Health Services Research)
Abstract Background Hypertension is the most commonly managed problem in general practice in Australia, but blood pressure control is not achieved for most patients. An important factor to consider in hypertension control is patient medication adherence. Use of dose administration aids (DAAs) could increase adherence to medicines and reduce the frequency of medication errors. We conducted a trial to evaluate adherence to DAAs in real-world conditions. This study is a process evaluation of the main trial. This stydy aims to understand the acceptability of DAAs from patients, providers, and carers perspectives and examine implementation barriers and facilitators of trial processes. Methods In-depth, semi structured interviews were conducted in an Australian general practice participating in a pilot randomised controlled trial evaluating a DAA-based strategy for people with high-risk primary and secondary cardiovascular disease. Interview topics included DAA acceptability, factors affecting adherence and trial implementation. Transcribed interview data were analysed thematically and interpretively. The consolidated framework for implementation research was used to guide our analysis. Results Nineteen interviews were conducted (16 participants or carers, 1 physician, 1 pharmacist and 1 DAA packaging company representative). All trial participants reported improved adherence, especially in those with prior poor adherence. Key barriers to DAA use included inertia to change, resistance from the pharmacist with regards to repackaging by an external provider, logistics of direct home delivery and lack of communication. A key facilitator to trial implementation was the therapeutic relationship of patients with the health care professionals. Conclusion The DAA strategy was generally acceptable to patients and the physician as a cardiovascular preventative strategy. Participants suggested a DAA-based strategy as particularly appropriate for those with prior poor adherence to medications. Trial registration ACTRN12620001239954. 19/11/2020.